2005
DOI: 10.1002/hep.20595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of celecoxib and naproxen on renal function in nonazotemic patients with cirrhosis and ascites

Abstract: Nonselective inhibition of cyclooxygenase (COX) by nonsteroidal anti-inflammatory drugs frequently induces renal failure in decompensated cirrhosis. Studies in experimental cirrhosis suggest that selective inhibitors of the inducible isoform COX-2 do not adversely affect renal function. However, very limited information is available on the effects of these compounds on renal function in human cirrhosis. This investigation consists of a double-blind, randomized, placebo-controlled trial aimed at comparing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 43 publications
0
45
0
1
Order By: Relevance
“…However, these agents should not be used in patients with advanced liver disease or cirrhosis because data are limited on their use in such patients. 24 …”
Section: Selective Cox-2 Inhibitorsmentioning
confidence: 99%
“…However, these agents should not be used in patients with advanced liver disease or cirrhosis because data are limited on their use in such patients. 24 …”
Section: Selective Cox-2 Inhibitorsmentioning
confidence: 99%
“…Being aware of the harmful eff ects of NSAID or aspirin on the gastric mucosa and renal function in patients with liver cirrhosis ( 38 ), NSAID / aspirin are being used in a more conservative attitude. Th e increasingly conservatively use of NSAID / aspirin is evidenced by the lower prevalence of NSAID / aspirin in cirrhosis patients either with (6.7 % ) or without (5 % ) EV bleeding in the current study in contrast to the 19 -35 % reported in previous studies ( 14,38,39 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In liver, COX-2 up-regulation has been linked to patients with chronic viral hepatitis B and C (15,16), cirrhosis (17,18), and hepatocellular carcinoma (17,19). We have previously observed that COX-2 expression is up-regulated in damaged livers after I/R (20).…”
mentioning
confidence: 99%